Motivação e deliberação da religião no espaço público - Marques, José Ronaldo de Oliveira (2022)
This work aims to debate about the religion in the public space. Habermas builds a concept of communicative reason in modernity considering the post-secularization that makes viable the religious discourse on societies largely secularized. For a better understanding, this work starts from a foundation of the religious discussion in societies largely secularized in post-secularization. Proceeding, we demonstrate that the author uses as theoretical references Kant and Hegel to substantiate his communication theory, connecting the perspective of faith and knowledge. Kant, before criticizing the faith itself, criticizes the pure reason, as the attempt of proving the existence of God is contradictory and full of antinomies. On the other hand, the young Hegel criticizes the statutory and positive faith influenced by Kant. For Hegel, the primitive Christian religion and the love instigate the intersubjectivity, however the people’s religion project lost its meaning with the secularization in the Modernity, while the Habermas’ communicative theory considers the subject-subject relation, distancing itself from the Kantian reason centered in the subject-object monologue. Otherwise, Hegel’s idea of rationality, according to Habermas, tried, through metacritique, to overcome the Kantian thought, but his idea of Absolute failed to decentralize reason. Therefore, we delineate the path of the Habermasian religious discourse, creating the conditions to think about a decentralized rationality. Habermas exploits the discourse principle “D”, based on the Kantian reason, of the communicational type, that also adheres to Hegel’s intersubjectivity. Thus, overcoming the transcendental and absolute subject, Habermas seeks the consensus through the communicative reason between the religious and non- religious citizens in the public sphere. This is justified by the postsecularization phenomenon which, through his theory of Communicative Action, imposes on the religion the translation of its faith and on the non-religious citizens the assimilation, with no loss to the affected in the discourse, maintaining the cooperation. Hence, the decentralized reason enables the religious discourse in the public space and the dialogue with the secular world in the process of cooperation through practical discourses.